Reformulasi Pendidikan Agama Bagi Anak-Anak Jalanan: Reformulating Religious Education for Street Children - Soebahar, Abd. Halim (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2002)
The growing number of street children in urban centres such as Jember poses a critical challenge to the effectiveness of religious education, which often fails to address their unique socio-economic realities. This study addresses the gap between conventional religious pedagogy and the lived experiences of marginalised youth by examining five key dimensions: their characteristics, religious knowledge, religious values, religious behaviour, and desired educational patterns. A qualitative approach was employed, involving life-history interviews, non-participant observation, and focus group discussions with 25 purposively selected street children from several locations in Kota Jember. The findings reveal that street children have developed a distinct and exclusive life philosophy, often ambivalent towards formal religious norms. Their religious knowledge remains limited and homogeneous, primarily derived from parents and schools, while peer influence leads to shifts in values and behaviours that mimic a